PROSES PENGOLAHAN LIMBAH ORGANIK SECARA KOAGULASI DAN FLOKULASI - Indriyati indriyati (BPPT)
Soya bean sauce waste water is an high organic wastewater and has dark colour, therefore it is diffi cult to degrade it biologically. Base on as mentioned above, it is tried to process it with coagulation and fl okulation use Alumunium sulphate and PAC which is added to wastewater with several dosis variation of Alumunium sulphate: 100, 200, 300. 250, and PAC with dosis 50, 100, 150, 200 ppm. Experiment result shows the experiment which use a match Alumunium sulphate and PAC as coagulant could give a good quality of processing and suitable with the treshhold of wastewater. The application of fl okulan Aquaklir 240 could help the performance of coagulan that can be seen from the fl oc size form.Key words : fl occulation, coagulation.